Total hip arthroplasty performed in a 13-year-old Girl with avasvular necrosis (AVN) of the left hip: A case report - Komang Agung Irianto (Bali Medical Journal, 2017)
Total hip arthroplasty (THA) is a commonly performed procedure in adults but rarely resorted to as a surgical option in the case of children. It is not only technical challenging, but the real staple is how to reach the decision. Until now arthrodesis is the primary option in the treatment plan for severe hip destruction. We are reporting the case of a 13-year-old girl who suffered left hip pain caused by unknown destruction of the joint. On physical examination, the girl presented a limping gait that was caused by severe pain and discrepancy between the lengths of both legs and also adduction contracture. The imaging suspected AVN feature without showing evidences for clear causal factors like Legg-Calve-Perthes disease (LCP), infection,  juvenile rheumatoid  arthritis (JRA), or slipped capital femoral epiphysiolysis (SCFE). We report a rare case of THA in girl who had had an unclear preoperative diagnostic.